PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAPKEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi Kasus Pada Pengguna Smartphone di Kota Jakarta Timur) - Muhammad Reva Andrian (2022)
This research model is a quantitative research that aims to determine and prove the effect of Brand Image. Product Quality, and Price on Purchasing Decisions of Samsung smartphones. This study uses the people of east Jakarta as a sample and the number of samples used is 100 respondents with the Non-Probability Sampling method with purposive type. The data collection technique uses a questionnaire using the Google Form Platform. The test tool used is Partial Least Square (PLS) as a test tool. The test used in this study is the statistical R test, Q test, F test and T test. The results of this study are Brand Image and Product Quality has a positive and significant effect on purchasing decisions, while price have no and no significant effect on purchasing decisions on Samsung smartphones.